Economic freedom and the quality of education. - Feldmann, Horst (Kyklos, 2025)
This paper finds robust evidence that economic freedom improves the quality of education. This is probably mainly because economic freedom incentivizes parents to invest in high‐quality education for their children and helps them to do so. It also incentivizes and helps both governments and private providers to deliver high‐quality education. The paper uses two different indicators of educational quality: PISA scores and the World Bank's harmonized test scores. The magnitudes of the estimated effects of economic freedom on both indicators are substantial. They are even larger once the indirect impact of economic freedom via GDP per capita and, to a lesser extent, once the indirect impact via government education expenditure is taken into account. The paper uses data on up to 49 countries for PISA scores and up to 137 countries for World Bank scores. It accounts for the endogeneity of economic freedom and controls for all major determinants of educational quality.